Understanding Youth Violence : Cases from Liberia and Sierra Leone - World Bank (Washington, DC, 2014)
Addressing youth issues is essential to promoting stability and preventing violence in fragile and conflict-affected states. However, there is little evidence that youth programming and policies have helped reduce violence in these settings. This can reflect the lack of understanding about youth issues and how problems affecting them encourage their participation in violence. This study set out to understand youth violence in Liberia and Sierra Leone, two countries in which there has historically been a great deal of youth participation in group violence, where the risk of youth mobilization into violence persists, and where interpersonal and gender-based violence are still a concern. In addition to having young populations, both countries have governments that have emphasized improving youths' lives by both reducing poverty and preventing violence. In turn, programming and policies in these (and many other conflict-affected) countries tend to be focused on employment generation due to the assumption that youth become prone to violent behavior as the result of economic exclusion (their inability to achieve a stable source of livelihood). The findings from this study will be useful to help governments (particularly of fragile and conflict-affected states) and donors better understand youth issues, design more effective interventions to address youth violence, and promote longer-term stability. The report begins with a review of literature on existing theories of youth exclusion and drivers of youth violence, with a greater focus on history of violence in West Africa. It proceeds with an outline of the study methodology for data collection, sample selection, and analysis. The analysis follows, highlighting key findings. The report concludes with recommendations for policies and youth programming.